Codonopsis pilosula polysaccharides attenuate Escherichia coli-induced acute lung injury in mice. Issue 15 (12th July 2022) - Gong, Zhiguo; Zhang, Shuangyi; Gu, Baichen; Cao, Jinshan; Mao, Wei; Yao, Yuan; Zhao, Jiamin; Ren, Peipei; Zhang, Kai; Liu, Bo
Abstract : Acute lung injury (ALI) is an inflammatory lung disease that is caused by bacterial infection. Abstract : Acute lung injury (ALI) is an inflammatory lung disease that is caused by bacterial infection. Lipopolysaccharide (LPS), a prototype pathogen-associated molecular pattern (PAMP) from Gram-negative bacteria such as Escherichia coli ( E. coli ), is an essential risk factor for ALI. LPS and E. coli induced the activation of mitogen-activated protein kinase (MAPK) and nuclear factor kappaB (NF-κB) signaling pathways, which led to the increasing immune molecule transcription, including pro-inflammatory cytokine and chemokine secretion. Codonopsis pilosula polysaccharides (CPPS) exhibit various biological activities and pharmacological effects. However, the effect of CPPS on ALI caused by LPS stimulation or E. coli infection remains unclear. Our results showed that CPPS (6.25, 12.5, 25, or 50 μg mL −1 ) could attenuate the secretion of TNF-α and IL-1β and impair the phosphorylation of ERK, p38 and p65 in E. coli -infected macrophages without causing toxic reactions. In addition to regulating the secretion of pro-inflammatory cytokines and the activation of MAPK and NF-κB signaling pathways, CPPS could enhance bacterial phagocytosis and intracellular killing in macrophages, and inhibit the bacterial growth of E. coli . In vivo experiments showed that CPPS attenuated LPS- and E. coli -induced lung damage in mice, which was characterized by decreased pro-inflammatory cytokine (TNF-α, IL-1β and IL-6) and chemokine (RANTES) production and production of the biomarkers of tissue damage (HABP2 and HMGB1) in the lungs. Altogether, this study demonstrated that CPPS have a protective effect on the lungs in LPS- and E. coli -induced ALI mouse models, suggesting that CPPS could be a potential drug for the treatment of ALI.